Achilles Region Soft-Tissue Defects: A Reconstructive Algorithm Based on a Series of 46 Cases - Innocenti, Marco; Innocenti, Alessandro; Ghezzi, Serena; Delcroix, Luca (Journal of Reconstructive Microsurgery, 2017)
Background Several options have been described for soft-tissue reconstruction in Achilles tendon region (ATR). The best procedure should be customized according to any single case taking into account the number of structures involved, the quality of the neighboring skin, and patient's general condition. The aim of this article is to describe a simplified reconstructive algorithm based on personal experience and reviewing literature.Methods Forty-four patients, who underwent ATR soft-tissue reconstruction between 1998 and 2016, have been retrospectively reviewed. Etiologies of the defect include the following: 18 posttraumatic, 10 postoncologic, 14 dehiscence/infection, and 2 chronic ulcers. Follow-up ranges between 12 and 96 months. Free flaps have been used in 30 cases (including two secondary surgeries due to propeller flap failure) and propeller flaps have been used in 16 cases.Results Thirty-six flaps survived uneventfully (78.3%). Total flap necrosis occurred in three cases (6.5%), namely, two propeller flaps and one free flap. Partial necrosis of the flap was observed in seven cases (15, 2%): three in the free flap group and four in the propeller group. The functional recovery was very good in all the patients without involvement of the tendon and also all the patients who underwent a simultaneous reconstruction of the tendon with different techniques recovered a full weight bearing and a satisfactory range of motion.Conclusion Propeller flaps are a valuable option for skin reconstruction in case of defects of small and medium size not involving the tendon. In case of larger defects and when a simultaneous ATR reconstruction is required, a free flap seems to be a better option.
Keywords: Achilles tendon reconstruction; soft tissue; algorithm